PENGEMBANGAN BAHAN AJAR INTERAKTIF MATERI HIMPUNAN BERBASIS ARTICULATE STORYLINE 3 - Seli Intan Oktoviyani; Dedi Muhtadi; Depi Setialesmana (LPPM Universitas Bina Bangsa, 2023)
This study aims to describe the development of interactive teaching materials based on articulate storyline 3 and students' responses to the developed teaching materials.The method used is Research & Development (R&D) with the Plomp model, which consists of preliminary investigation; design; realisation/construction; test, evaluation, and revision; and implementation. This research produced interactive teaching materials in the form of an application with the name ZetaZoo Story -Himpunan-. Data collection techniques were conducted through interviews and questionnaires. The data were obtained from two media experts, two material experts, and seventh grade students of SMP Negeri 8 Tasikmalaya. Teaching materials validated by experts are measured based on technical quality as well as content quality and objectives. The results of the validation of teaching materials by media experts through technical quality assessment state that interactive teaching materials are included in the very feasible category. In addition, the material quality assessment by material experts states that interactive teaching materials are included in the very feasible category. Instructional quality assessment is obtained through the implementation of teaching materials to students and gets an average percentage of 80% in the good category. Based on these results, the interactive teaching materials for set materials that have been developed get a good response from students